Effects of increasing tile drainage and seasonal weather patterns on phosphorus loading from three major Canadian Lake Erie tributaries - Tedeschi AC; Fortier RA; Chow-Fraser P (Elsevier, 2024)
Tile-drainage area has expanded across the Canadian Lake Erie watershed in recent decades, and effects on phosphorus (P) loading are unclear. Eleven years (2010 to 2021) of daily P, total suspended solids (TSS), discharge, and climatological data were aggregated from three Canadian tributaries that form a gradient of tiled areas: East Sydenham River (ESR, 60% tile), Thames River (TR, 48% tile), and Grand River (GR, 23% tile). Instead of using traditional seasons (winter, spring, summer, fall), we classified seasons by air temperature to highlight hydrological periods of importance for P loss through tile drains. Seasons included frozen (<−3.2 °C), thawing (−3.2 – 6.7 °C), bare (6.7 – 15.9 °C), and growing (>15.9 °C). Nonparametric comparisons revealed that during every season, the ESR and TR had significantly higher soluble reactive P (SRP) and total P (TP) concentrations than the GR. For %SRP, the ESR was significantly higher than the other rivers during every season, while for TSS, the GR was significantly higher than the other rivers during every season. Only during the thawing season were positive relationships observed in every river between year-over-year tile-drainage proportion and associated P loadings and concentrations. The ESR was the only river to yield significant relationships between tile drainage and P in all seasons except the frozen season. Our findings suggest that increases in tile-drainage area can lead to increases in SRP loading to Lake Erie from Canadian tributaries, especially during the thawing season. However, effects of tile drainage are moderated by differences in soil texture, land-use-land-cover, climate, and point sources.
Keywords: 41 Environmental Sciences; 31 Biological Sciences; 3103 Ecology; 4104 Environmental Management; 15 Life on Land